Dysmenorrhoea during the COVID-19 lockdown: a study of women in the age group 18-45 years in Goa, India - Mukherjee, Taran; Afonso, Shiara; Kenkre, Trusha; Usgaonkar, Ojal; Dias, Amit (International Journal of Research in Medical Sciences, 2022)
Background: Dysmenorrhea can be incapacitating and affect a woman’s quality of life and productivity. Our aim was to ascertain the prevalence and attributes of dysmenorrhea among women aged 18-45 years in the state of Goa, India; the attitude towards dysmenorrhea and management methods; and to also understand the impact of the COVID-19 lockdown on women experiencing dysmenorrhea. Methods: A self-administered Google form was circulated and analysed using STATA-statistical software version 16. The study was conducted under the observation of Goa Medical College, in the months of May and June of 2020. Results: 87.7% (664) of participants experienced dysmenorrhea of which 72% had moderate-severe pain during menses. The pain lasted for 1-4 days in 98.6% of the respondents. A total of 69.25% women took some measures to relieve the pain; however only 27% of them sought professional medical help. During the lockdown 17% participants noticed a change in their periods. A change in the method of pain management was reported in 12.05% of the women. It was noted that the younger age group reported more changes in their periods during the lockdown. Conclusions: Dysmenorrhea impacted the lives of a large proportion of women. Even though some experienced incapacitating pain, many women did not seek medical advice. The lockdown due to the COVID-19 pandemic affected the menstrual cycle including dysmenorrhoea and its management. The high prevalence of dysmenorrhea coupled with inadequate utilisation of health services, makes it all the more important to utilise the results of this study in order to educate women about the effective methods of treatment.